If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -6x = 36 Reorder the terms: -6x + 4y = 36 Solving -6x + 4y = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. -6x + 4y + -4y = 36 + -4y Combine like terms: 4y + -4y = 0 -6x + 0 = 36 + -4y -6x = 36 + -4y Divide each side by '-6'. x = -6 + 0.6666666667y Simplifying x = -6 + 0.6666666667y
| 11x^2-4x+2=0 | | 4x+1=9x-20 | | 2ac^2+ac=b^2+3b | | 2(x-8)-(x-4)=3(x+5)+3 | | b^2+3b=4b^2 | | 3r+10=5r+2 | | 0.273y-18.3=.36-2.7y | | X^2-28=12x | | 0.723y-183=0.36-2.7y | | x^2+49y^2=0 | | x+4/4-2x-1/2=x-2/4 | | 2(2x+5)=3(x+3) | | 5x+221=13x-11 | | 6y+21=4y-4 | | x^2+49y^2=64 | | 168-7x=38x+18 | | x^2+49y^22=64 | | 168-7x=38+18 | | 8x+8(3x+10)=32 | | 12-7x=30+21x | | x+(x*.088)=20 | | 10x-12=78 | | 2q+12=5q+3 | | 3(x+4)=2x-5 | | 49-10x=8x+23 | | 3x-12-x+2=2x-4 | | 2x+13=41-7x | | 7-9x=87-23x | | 2(2-x)=(x+3) | | -4-3x=14-19x | | 6=-10-p/5 | | -4(x+5)=28 |